Preliminary Investigation of Cardiovascular–Renal Disorders in Dogs with Chronic Mitral Valve Disease. (22nd September 2016) - Martinelli, E.; Locatelli, C.; Bassis, S.; Crosara, S.; Paltrinieri, S.; Scarpa, P.; Spalla, I.; Zanaboni, AM.; Quintavalla, C.; Brambilla, P.
Abstract : Background: Veterinary literature lacks data about cardiovascular–renal disorders (CvRD) and cardiorenal‐anemia syndrome (CRAS) in dogs. Hypothesis: A direct correlation exists between ACVIM class and IRIS stage; chronic kidney disease (CKD) complicates chronic mitral valve disease (CMVD) more often than does anemia in dogs. Animals: One hundred and fifty‐eight client‐owned dogs with CMVD. Methods: Signalment, physical examination findings, electrocardiography, thoracic radiographs, echocardiography, and blood analysis were retrospectively evaluated to assess the prevalence of CKD and anemia in dogs with CMVD and to investigate the relationships among ACVIM class, IRIS stage, and survival. Results: The prevalence of CKD and anemia in dogs with CMVD was significantly higher than in the general population of dogs. Dogs being treated for heart failure had a significantly higher prevalence of CKD than did dogs that had not received treatment. A statistically significant direct correlation was found between ACVIM class and IRIS stage. Severe heart disease, severe renal disease or both, furosemide administration, and advanced age at diagnosis of heart disease were associated with shorter survival time. Survival time of dogs affected by CvRD was statistically shorter than survival time of dogs affected by CMVD alone. Conclusion and Clinical Relevance: Chronic mitral valve disease is associated with increased prevalence of CKD and anemia in dogs. Treatment for medical management of heart failure may play a role in inducing CKD. Class of heart disease and IRIS stage were directly correlated. Cardiovascular–renal disorders decrease survival time compared to the only presence of CMVD alone, whereas anemia does not play a central role in worsening heart function.